Implementasi Nilai Binadamai di Masyarakat Sunda dalam Kesenian Reak - Sulhi Sulhi (Jurnal Iman dan Spiritualitas, 2021)
Performing arts are not created by accident, but they are made based on the values, world views, and beliefs of artists and their publics as part of a socio-cultural activity of society. Artists create, package, and create performing arts as part of creative efforts carried out by a constructive spirit through symbolic actions. This study aims to determine the implementation of one of the Sunda Reak arts in creating a peaceful society following the values of Indonesian multiculturalism. This research method uses a descriptive qualitative approach to describe Reak's artistic values in creating a quiet life in society. In ancient times, ancient ancestors implemented peacebuilding in future generations through activities cultured as traditions in the community. The findings of this study indicate that Reak art is not just an entertainment show because some sources say that tradition is an ancestral heritage that is so sacred and becomes a necessity for social beings in living life.